Total quality management and its impact on the performance of workers in the health sector: A study of its application to government sector hospitals in Riyadh - Al-Mutairi, Aref Abdulaziz; Al Hussainah, Mardi Mubarak; Al-Enezi, Mamdouh Fahad; Al-Mutairi, Fayez AbdulMohi; Al-Mutairi, Razan Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the impact of total quality management on the performance of workers in the health sector by applying to hospitals in the city of Riyadh, as well as to identify the level of total quality management and the performance of workers in the health sector in Saudi Arabia. In government hospitals in Riyadh, the study sample consisted of (265) employees of government hospitals in Riyadh. A statistic at the level of significance (0.01), between the total degree of total quality management and the performance of workers in the Saudi health sector among workers in government hospitals in Riyadh. In light of the results, the study recommends the necessity of the senior management of Riyadh hospitals to adopt the application of the total quality management system as a framework for performance development and continuous improvement for all external and internal hospital operations. And the necessity of enacting laws and regulations that contribute to overcoming the obstacles that could prevent the application of total quality management, by providing an effective accounting system for all health sector institutions. In addition, the importance of developing strategic plans for total quality by all the health sector and the Saudi Ministry of Health, based on the needs of the beneficiaries. In addition, the need to develop unified policies for a system of material and moral motivation of incentives rewards and promotions according to excellence in performance, and to create an appropriate work environment to stimulate the performance of workers in the health sector.